Evektifitas Kebijakan Open Data terhadap Partisipasi Publik dan Akuntabilitas Pemerintahan di Kabupaten Poso - Herlan Lagantondo; Abdi Sakti Walenta (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study examines the effectiveness of Open Data policies in enhancing public participation and government accountability in Poso Regency. Utilizing a library research approach, it analyzes secondary data to assess how open access to public data fosters transparency and civic engagement. The findings reveal that Open Data, through initiatives like the Village Information Sistem (SID), improves administrative efficiency and financial oversight, yet faces challenges such as limited digital literacy, unstable internet connectivity, and public apathy. These factors hinder optimal participation and accountability. The study highlights the need for digital literacy programs, improved infrastructure, and inclusive leadership to maximize the policy’s impact. Open Data serves as a catalyst for sustainable local governance and development in Poso.